Diagnosis and management of gastroesophageal reflux disease - Henry, Maria Aparecida Coelho de Arruda [UNESP] (FapUNIFESP (SciELO), 2014)
Gastroesophageal reflux disease (GERD) is probably one of the most prevalent diseases in the world that also compromises the quality of life of the affected significantly. Its incidence in Brazil is 12%, corresponding to 20 million individuals. OBJECTIVE: To update the GERD management and the new trends on diagnosis and treatment, reviewing the international and Brazilian experience on it. METHOD: The literature review was based on papers published on Medline/Pubmed, SciELO, Lilacs, Embase and Cochrane crossing the following headings: gastroesophageal reflux disease, diagnosis, clinical treatment, surgery, fundoplication. RESULTS: Various factors are involved on GERD physiopathology, the most important being the transient lower esophageal sphincter relaxation. Clinical manifestations are heartburn, regurgitation (typical symptoms), cough, chest pain, asthma, hoarseness and throat clearing (atypical symptoms), which may be followed or not by typical symptoms. GERD patients may present complications such as peptic stenosis, hemorrhage, and Barrett's esophagus, which is the most important predisposing factor to adenocarcinoma. The GERD diagnosis must be based on the anamnesis and the symptoms must be evaluated in terms of duration, intensity, frequency, triggering and relief factors, pattern of evolution and impact on the patient's quality of life. The diagnosis requires confirmation with different exams. The goal of the clinical treatment is to relieve the symptoms and surgical treatment is indicated for patients who require continued drug use, with intolerance to prolonged clinical treatment and with GERD complications. CONCLUSION: GERD is a major digestive health problem and affect 12% of Brazilian people. The anamnesis is fundamental for the diagnosis of GERD, with special analysis of the typical and atypical symptoms (duration, intensity, frequency, triggering and relief factors, evolution and impact on the life quality). High digestive endoscopy and esophageal pHmetry are the most sensitive diagnosctic methods. The clinical treatment is useful in controlling the symptoms; however, the great problem is keeping the patients asymptomatic over time. Surgical treatment is indicated for patients who required continued drug use, intolerant to the drugs and with complicated forms of GERD.

A doença do refluxo gastroesofágico (DRGE) é, provavelmente, uma das doenças mais prevalentes no mundo que compromete significativamente a qualidade de vida. Sua incidência no Brasil é de 12%, o que corresponde a 20 milhões de indivíduos. OBJETIVO: Atualizar o manuseio da DRGE e as novas tendências no diagnóstico e tratamento, revendo as experiências internacional e brasileira sobre o tema. MÉTODO: Foi realizada revisão da literatura baseada em artigos publicados no Medline/Pubmed, SciELO, Lilacs, Embase e Cochrane cruzando os seguintes descritores: doença do refluxo gastroesofágico, diagnóstico, tratamento clínico, cirurgia, fundoplicatura. RESULTADOS: Vários fatores estão envolvidos na fisiopatologia da DRGE, sendo o mais importante o relaxamento transitório do esfíncter inferior do esôfago. As manifestações clínicas são azia, regurgitação (sintomas típicos), tosse, dor torácica, asma, rouquidão e pigarro (sintomas atípicos), que podem ser seguidos ou não de sintomas típicos. Pacientes com DRGE podem apresentar complicações como estenose péptica, hemorragia e esôfago de Barrett, que é o fator predisponente mais importante para adenocarcinoma. O diagnóstico deve ser baseado na anamnese e os sintomas devem ser avaliados em termos de duração, intensidade, frequência, fatores precipitantes e relevância, padrão de evolução e impacto na qualidade de vida do paciente. O diagnóstico exige confirmação com exames diferentes. O objetivo do tratamento clínico é aliviar os sintomas e o tratamento cirúrgico é indicado para os que necessitam de uso contínuo de drogas, com intolerância ao tratamento clínico prolongado e com complicações. CONCLUSÃO: A anamnese é fundamental para o diagnóstico de DRGE, com análise especial dos sintomas típicos e atípicos. Endoscopia digestiva alta e pHmetria esofágica são os métodos diagnósticos mais sensíveis. O tratamento clínico é útil no controle dos sintomas; no entanto, o grande problema é manter os pacientes assintomáticos ao longo do tempo. O tratamento cirúrgico é indicado para pacientes que necessitaram o uso contínuo de drogas, intolerantes às drogas e com formas complicadas da DRGE.
Diagnosis and management of gastroesophageal reflux disease
Keywords: Gastroesophageal reflux; Diagnosis; Therapeutics; Fundoplication; Surgery; Refluxo Gastroesofágico; Diagnóstico; Terapêutica; Fundoplicatura; Cirurgia